2020
DOI: 10.1039/d0ra03160g
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic nanocrystal reductase to promote green asymmetric synthesis

Abstract: Geotrichum candidum acetophenone reductase (GcAPRD) nanocrystal reduces broad kinds of ketones to their corresponding (S)-alcohols with excellent enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…27 Some research reported that the affinity between the His tag on the proteins and the metal ions played a role in the nanocrystal formation. 28,47,48 2.2. Variability in the Nanocrystal Formation Process and Its Morphology.…”
Section: Enzyme Immobilization Through Organic−inorganic Nanocrystal ...mentioning
confidence: 99%
See 3 more Smart Citations
“…27 Some research reported that the affinity between the His tag on the proteins and the metal ions played a role in the nanocrystal formation. 28,47,48 2.2. Variability in the Nanocrystal Formation Process and Its Morphology.…”
Section: Enzyme Immobilization Through Organic−inorganic Nanocrystal ...mentioning
confidence: 99%
“…An alcohol dehydrogenase (2 mg/mL) was immobilized with the nanocrystal formation method, and parallel hexahedron structures mixed with the spongelike structure were observed. 48 Furthermore, the metal ion in the nanocrystal formation process can be varied: for instance, Cu 2+ , Ca 2+ , Mn 2+ , Zn 2+ , Co 2+ , and Fe 2+ can be used. 15 54 Each metal ion used resulted in a different nanoflower structure and enzyme activity.…”
Section: Enzyme Immobilization Through Organic−inorganic Nanocrystal ...mentioning
confidence: 99%
See 2 more Smart Citations
“…[46][47][48][49][50][51][52] In our previous works, we immobilized GcAPRD with nanomaterials such as organic-inorganic nanocrystals and graphene-based nanomaterials. 53,54 However, flow process operation using the immobilized GcAPRD was not achieved, because the immobilized enzymes were too small to hold in the column in the flow process.…”
Section: Introductionmentioning
confidence: 99%